Antidiabetic activities of Cinnamomum zeylanicum and Tinospora crispa on adipocytes - Bakhtiar, M. Taher; Mohamed Amiroudine, Mohamed Zaffar Ali; Solachuddin Jauhari, Arief Ichwan; Kaderi, Mohd Arifin; Darnis, Deny Susanti (2011)

(untitled)
The effects of Cinnamomum burmannii and Tinospora crispa on differentiation and glucose uptake in 3T3-L1 adipocyte cells were studied. Cells were stimulated to differentiate with differentiation cocktail containing Dulbecco’s modified Eagle’s medium (DMEM) with 10% fetal bovine serum (FBS), 0.25 µM dexamethasone, 0.5 mM 3-isobutyl-1-methyl-xanthine and 167 µM insulin. 3T3-L1 preadipocytes were treated with various concentrations of the extracts in the presence of differentiation cocktail. Insulin was used as a positive control. The ability of the extracts to induce differentiation in preadipocytes was examined by measuring fat accumulation using oil red O staining. Our results showed that C. burmannii and T. crispa was statistically significant in inducing preadipocyte into mature adipocyte at dose of 0.1 mg/mL (p < 0.001) and 0.5 mg/mL (p < 0.05), respectively. Glucose uptake activity was investigated in differentiated adipocytes using a radioactive-labelled glucose by Liquid Scintillation Counter. The activities in the glucose uptake between untreated and treated cells showed that both plants were statistically significant compared metformin (1 mM), but not significant compared to sodium orthovanadate (5 mM). In conclusion, these results suggest that both plants were effective in inducing adipocyte differentiation and stimulate glucose uptake.